Comparison of hydrogen, halogen, and tetrel bonds in the complexes of HArF with YH3X (X = halogen, Y = C and Si). Issue 23 (16th February 2016) - Liu, Mingxiu; Li, Qingzhong; Li, Wenzuo; Cheng, Jianbo; McDowell, Sean A. C.
Abstract : Ab initio calculations were performed in order to find equilibrium structures with tetrel, hydrogen or halogen bonds on the potential energy surfaces of the complexes formed between HArF and YH3X (X = halogen, Y = C and Si). Abstract : Ab initio MP2/aug-cc-pVTZ calculations were performed in order to find equilibrium structures with Y⋯F tetrel bonds, X⋯H hydrogen bonds or X⋯F halogen bonds on the potential energy surfaces of the complexes formed between HArF and YH3 X (X = halogen, Y = C and Si). For the CH3 X complexes, the hydrogen-bonded complex is the most stable, while the tetrel-bonded complex is the most stable of the SiH3 X complexes. The H–Ar stretch vibration exhibits a red shift for the hydrogen bond but a blue shift for the tetrel and halogen bonds. The hydrogen bonds in the CH3 X and SiH3 X complexes, as well as the tetrel bonds in the SiH3 X complexes, are governed by a combination of electrostatic and polarization energies, exhibiting partially covalent character with negative energy densities and a substantial amount of charge transfer.